The genus Rhynchosia (Leguminosae, Papilionoideae, Phaseoleae) in Brazil - Bezerra, Luísa Maria De Paula Alves [UNESP] (2019)
Rhynchosia presents a pantropical distribution, with two main centers of diversity for about 230 species, one in Africa (ca. 140 spp.) and the other in the American continents, where 55 species are recorded. This work consists in a taxonomic study of the genus Rhynchosia in Brazil where 19 species were recorded: Rhynchosia arenicola, R. balansae, R. claussenii, R. corylifolia, R. diversifolia, R. edulis, R. hauthalii, R. lateritia, R. leucophylla, R. lineata, R. melanocarpa, R. minima, R. naineckensis, R. phaseoloides, R. platyphylla, R. reticulata, R. rojasii, R. senna, R. schomburgkii. Two new occurrences were registered for Brazil, R. claussenii in Maranhaõ state and R. edulis in Espírito Santo state. A morphological study was carried out to re-evaluate the diagnostic characteristics for prompt identification of the species, facilitating the delimitation of taxa. In addition, illustrations, descriptions, comments, and geographical distribution data were provided.